PENGARUH MOTIVASI KERJA, PELATIHAN KERJA DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA BANK MUAMALAT INDONESIA CABANG KOTA KEDIRI - Ariyanti, Bella Putri; Sutapa, Heru; Jatmiko, Udik (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 03 (2023): EDISI OKTOBER - JANUARIDO - 10.32503/ammer.v2i03.3427, 2023)
This study aims to determine the effect of work motivation, job training and discipline on employee performance at Bank Muamalat Indonesia, Kediri Branch. The variables of this research are Work Motivation, (X1), Job Training (X2), Discipline and Employee Performance (Y). This study uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. While the analysis used is the validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and the coefficient of determination. Sampling in this study used a saturated sample with consideration of all employees of Bank Muamalat Indonesia Kediri Branch, amounting to 42 people based on the results of research conducted. (1) partially work motivation has a significant effect on employee performance with a significant (2) partially job training has a significant effect on employee performance with a significant (3) partially discipline has a significant effect on employee performance with a significant (4) Simultaneously Work Motivation, Job Training and Discipline have a significant effect on employee performance with a significant